Profiles and factors associated with schizophrenia in eastern Ethiopia: A matched case-control study - Mohammed, Fethia; Geda, Biftu; Yadeta, Tesfaye Assebe; Dessie, Yadeta (Frontiers in Psychiatry, 2022)
Abstract Background: Despite its strong hereditary and genetic connections, there are other factors reported to be linked to schizophrenia, but not well studied in Eastern Ethiopia. Objective: This study was aimed to investigating the potential determinants of schizophrenia in Eastern Ethiopia Methods: A matched case-control study was conducted in two public hospitals from December 1, 2021, to January 30, 2022. Cases were patients with schizophrenia who visited the hospitals, and controls were healthy individuals without any mental illness who visited the same hospitals. A questionnaire was used to collect the data. Cases and controls were matched using age and sex. STATA-14 was used for analysis. A conditional logistic regression with an adjusted odds ratio (AOR) and a 95% confidence interval (CI) was applied to identify the determinants. P-values of < 0.05 were used to build the final model as a measure of statistical significance. Results: The mean age of the study participants' group was 28.6 (±8.44) years, mean age for cases was 28.7(±8.5) ranging from 18 to 56 years; and the mean age for the controls was 28.4 (+8.5), ranging from 18 to 60 years. About 181 (83.03%) of the participants were male. The odds of having schizophrenia was about 12.2 times higher among participants with a family history of mental illness (AOR: 12.21; 95 % CI: 4.83_30.00). The odds of having schizophrenia was 4.5 times higher among polysubstance users (AOR: 4.45; 95% CI: 1.28–5.45) and 2.8 times higher among khat consumers (AOR: 2.82; 95 % CI: 1.23__6.45) compared to their counterparts Conclusions: Our findings reveal that genetic risk factors and some modifiable behaviors were associated with schizophrenia in eastern Ethiopia. Special attention should be given for those who is at risk at all level